Cost Management as A Strategy for Competitiveness in Private Higher Education Institutions in Cabinda (London Journal of Research In Management & Business, 2025)
This dissertation, which addresses Cost Management as a Strategy for the Competitiveness of Private Higher Education Institutions (PHEIs) in Cabinda, aims to demonstrate its importance as a strategic tool for enhancing competitiveness. The study seeks to understand how efficient cost management practices promote the rational use of resources and improve institutional performance, considering that PHEIs in Cabinda face a high dependency on student tuition fees and a predominantly fixed cost structure, which limits the precision of expense allocation. A qualitative case study approach was adopted, focusing on the Instituto Superior Politcnico de Cabinda (ISPCAB), with a descriptive and explanatory nature, based on the hypothetical-deductive method. Data collection was carried out through semi-structured interviews and document analysis, involving financial, administrative, and operational managers, as well as internal ISPCAB documents. Findings revealed that the implementation of the Activity-Based Costing (ABC) system enabled a more effective allocation of costs by activity and subsequently by academic program, ensuring greater cost traceability to support decision-making. Cost management showed a direct positive impact on the institutions operational efficiency and financial sustainability. The main hypothesis was validated, confirming that effective cost management enhances competitiveness by optimizing resource use and improving profitability. A balanced relationship was identified between operational costs and revenues (17.5%), as well as positive profitability across the programs analyzed, with particular emphasis on the International Relations course, which recorded the highest profit margin (85.61%). Additionally, the application of internal benchmarking, based on the ABC methodology, proved to be a valuable complementary strategic tool by enabling the identification of internal best practices and significant performance disparities among academic programs. It is concluded that cost management, particularly through the ABC system, is crucial for the efficiency, sustainability, and competitive advantage of private higher education institutions in Cabinda, as it empowers more coherent and proactive decision-making at ISPCAB.
Keywords: Approximate Nearest Neighbor; Dynamic Indexing; Advertisement Retrieval; Performance Degradation; Graph-based Algorithms; Performance; Security; Effect; Momo Data promoter agent and MTN Ivory Coast.; organizational culture; Rationality; cohesion; team building; socio-economic factors; economic actors; ethnic identity; Inventory Management; Supply Chain Optimization; Appian; Business Process Management; Low-Code Development; Robotic Process Automation; Real-Time Analytics; Procurement Automation; Logistics Tracking; competitiveness; Cost Management in Higher Education; Activity-Based Costing (ABC)